Arterial involvement of lower limbs in peripheral artery disease - the difference between diabetics and non-diabetics - Tanzeela Khan; Naheed Khan; Sajida Qureshi (Journal of the Pakistan Medical Association, 2024)
Objective: To detect peripheral artery disease in diabetic and non-diabetic individuals. Method: The case-control study was conducted from October 2018 to September 2019 at Ruth K.M. Pfau Civil Hospital, Karachi, and comprised diagnosed diabetic patients with random blood sugar Greater than or Equal to 200mg/dl in group A, and healthy non-diabetic subjects in group B. Ankle brachial pressure index was measured and mean luminal diameters of lower limb arteries were compared using colour Doppler ultrasonography. Data was analysed using SPSS 21. Results:Of the 82 subjects, 41(50%) were in each of the 2 groups. The sample had 42(51.2%) males and 30(48.8%) females with overall mean age of 53.9±5.07 years (range 44-60 years). There was significant difference in the ankle brachial pressure index values between the groups (p=0.004). There was also a significant difference in the mean luminal diameters of distal arteries (p=0.001), while there was no significant difference in proximal arteries (p>0.05). Conclusion: The diabetics were more prone to developing peripheral arterial disease than nondiabetics. Key Words: Blood Glucose, Ankle, Arteries, Ultrasonography, Angiopathies.